Cover-Copy-Compare for Multiplication With Students With Emotional and Behavioral Disorders: A Brief Report. (November 2019) - Schrauben, Kristen S.; Dean, Andrew J.
A multiple-baseline across participants design was used to investigate the effect of the Cover-Copy-Compare (CCC) intervention on multiplication-fact fluency for students with emotional and behavioral disorders (EBD). Although CCC is a well-researched intervention for mathematics, limited research has been conducted with students with EBD even though these students often struggle academically. Results indicate that a functional relation was established between CCC and an improved number of digits correct per minute for multiplication problems for only one of three elementary-age boys with EBD. Tau-U effect sizes ranged from no effect for one participant to a large effect for another participant. The length of the intervention and the initial level of a student's skills may be related to the effectiveness of CCC for students with EBD and should be explored in future studies.